In vitro Mycobacterial Growth Inhibition in South Korean Adults With Latent TB Infection - Lee, Hyejon; Kim, Jungho; Kang, Young Ae; Kim, Deok Ryun; Sim, Bora; Zelmer, Andrea; Fletcher, Helen A.; Dockrell, Hazel M.; Smith, Steven G.; Cho, Sang-Nae (Frontiers in Immunology, 2019)
Background: It is important to understand the ability to inhibit mycobacterial growth in healthy adults who would have been Bacillus Calmette-Guérin (BCG) vaccinated in childhood as this group will be the potential target population for novel booster TB vaccine trials. In this study we investigated not only the long-term immunity induced by childhood BCG vaccination but also protective immunity in terms of the ability to inhibit mycobacterial growth in those who were BCG vaccinated in childhood, with evidence of recent or remote TB infection. Methods: We measured the baseline immune response using a functional mycobacterial growth inhibition assay (MGIA) as a novel approach and an intracellular cytokine staining (ICS) assay as a reference approach in healthy adults, with different status of Mycobacterium tuberculosis (Mtb) infection. Results: Based on MGIA responses in historically BCG-vaccinated healthy adults, demographical characteristics including age and gender did not affect mycobacterial growth inhibition in PBMC. However, the uninfected healthy control (HC) group showed a greater ability to inhibit mycobacterial growth compared with the latent TB infection (LTBI) group (P = 0.0005). In terms of the M.tuberculosis antigen-specific T-cell immune response in diluted whole blood quantitated using an ICS assay, the LTBI group had a higher frequency of polyfunctional CD 4+ T cells compared with the HC group (P = 0.0002), although there was no correlation between ICS and the MGIA assay. Conclusion: The Mtb infection status had a significant impact on mycobacterial growth inhibition in PBMC from healthy adults in South Korea, a country with an intermediate burden of tuberculosis, with healthy controls showing the greatest mycobacterial growth inhibition.